The Elasticity of Investment and the Number of Productive-Age Population on Economic Growth in Parigi Moutong Regency - Wulan, Sri; Nurnaningsih, Nurnaningsih; Yohan, Yohan; Suirlan, Rita; Sading, Yunus (Transpublika Publisher, 2025)
This research seeks to examine how investment elasticity and the size of the working-age population impact the economic development in Parigi Moutong Regency. The study utilises a quantitative methodology, specifically employing multiple linear regression analysis. The data analysed consist of secondary time series data from 2010 to 2023 sourced from the Central Statistics Agency and other pertinent organisations. The findings of the investigation reveal that investment elasticity positively and significantly influences economic growth, whereas the number of productive-age individuals does not have a notable individual impact. Nonetheless, both factors collectively have a substantial impact on economic growth, as evidenced by a 90.8 percent coefficient of determination. These results shed light that enhancing investments plays a pivotal role in advancing regional economic growth, while strategies for empowering the workforce should be tailored more effectively. This study recommends that local governments integrate investment enhancement policies with human resource quality improvement to achieve inclusive and sustainable economic development.